Pengaruh Pembiayaan Mudharabah dan Pembiayaan Musyarakah Terhadap Laba Bersih PT. Bank BRI Syariah - Fitria Yulia Sari; Nahruddien Akbar (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This research has the objective of knowing and testing mudharabah and musyarakah financing whether or not there is an effect on net income at PT Bank BRI Syariah in 2018-2020. This research uses a quantitative descriptive method using secondary data derived from financial reports in the form of mudharabah financing data, musyarakah financing and net profit after tax from 2018 to 2020. This research uses an analytical tool, namely multiple linear regression. The SPSS 23.0 application was used to test the data in this study. Mudharabah and musyarakah financing based on the results of data analysis show that the net income together has a significant effect. This data analysis test shows that mudharabah financing on net income does not have a significant effect, meaning that if there is an increase or decrease in mudharabah financing, it will not affect the bank's net profit. Otherwise, musyarakah financing has a significant and positive effect on net income, meaning that the greater the income earned through musyarakah financing, the higher the Bank's net profit.